GREEN ACCOUNTING, KINERJA KEUANGAN, UKURAN PERUSAHAAN, DAN PERPUTARAN TOTAL ASET SEBAGAI DETERMINAN PROFITABILITAS - Enggar Nila Az Zahra; Rusliyawati Rusliyawati; Gita Desyana (Jurnal Akuntansi dan Keuangan, 2024)
The query is asking about the impact of green accounting, environmental performance, company size, and total asset turnover on the profitability of companies. The study uses a quantitative approach, analysis involves multiple regression analysis using SPSS 26. The data source was obtained using the purposive sampling method with predetermined criteria, and a total of 17 companies in the consumer non-cyclical sector were obtained within the research period from 2019 to 2023. The results of the study indicate that green accounting and company size do not have a significant impact on profitability individually. However, Environmental Performance and Total Asset Turnover partially have a significant impact on profitability. Companies can increase transparency and detail in environmental management, and optimize resource management to achieve maximum profits.